2015
DOI: 10.1007/s11130-015-0506-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects Associated with Quinoa Consumption and Implications for Research Involving Humans: a Review

Abstract: Quinoa is a pseudo-grain consumed as a dietary staple in South America. In recent years, consumer demand for quinoa in the developed world has grown steadily. Its perceived health benefits have been cited as a driving force behind this trend, but there are very few human studies investigating the impact of quinoa consumption. The aim of this review was to identify physiological effects of quinoa consumption with potential for human health. A critical evaluation of animal model studies was conducted. The qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…Velarde-Salcedo et al 2012investigated and revealed the ability of quinoa seed peptide to prevent the activation of dipeptidase dipeptidyl enzyme, in addition, to conduct the effects of this peptide in lipid accumulation in adipocyte rats cultures. Simnadis et al (2015) investigated physiological effect of consuming quinoa seeds to decrease weight gain and improve lipids profile. These physiological effects were attributed to the presence of protein, saponin, and 20-hydroxyecdysone in quinoa seeds, in addition to increasing the permeability of intestinal epithelial cell, decrease the capacity to nutrients active absorption for development and growth of animals.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Velarde-Salcedo et al 2012investigated and revealed the ability of quinoa seed peptide to prevent the activation of dipeptidase dipeptidyl enzyme, in addition, to conduct the effects of this peptide in lipid accumulation in adipocyte rats cultures. Simnadis et al (2015) investigated physiological effect of consuming quinoa seeds to decrease weight gain and improve lipids profile. These physiological effects were attributed to the presence of protein, saponin, and 20-hydroxyecdysone in quinoa seeds, in addition to increasing the permeability of intestinal epithelial cell, decrease the capacity to nutrients active absorption for development and growth of animals.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…It also has the potential to contribute to food security in other regions of the developing word [15]. Compared with other grains, like wheat, corn and rice, quinoa has a higher protein content, contains all essential amino acids, and is easy to digest as it is gluten free [10][11][12][13][14]. Being a strategic Andean crop in the region, quinoa has attracted political and research interest since 1999.…”
Section: Quinoa and Food Securitymentioning
confidence: 99%
“…Smallholders face different constraints to crop production and marketing than large-scale producers and might have different preferences for certain traits of improved quinoa varieties. For example, taste preference in Andean regions where quinoa belongs to the traditional diet may differ from taste preferences in international markets where quinoa has become healthy food type that has the highest content of protein compared with conventional grains like wheat, corn and rice [10] and that contains all essential amino acids [11], is gluten-free [12,13] and easy to digest [14]. In addition, one of the major impediments to reaching high productivity in the Andes region is quinoa's susceptibility to mildew, a plant disease caused by fungi [4,15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, quinoa is a good source of vitamins, oil with high linoleate and linolenate content (55–66% of the lipid fraction), natural antioxidants such as α- and γ-tocopherol, and a wide range of minerals (Repo-Carrasco et al, 2003; Vega-Gálvez et al, 2010; Fuentes and Bhargava, 2011; Stikic et al, 2012; Ruiz et al, 2014). Interestingly, quinoa consumption may lead to comparatively lower weight gain, and improved lipid profile and potential antioxidant effects, physiological outcomes that have been linked to bioactive compounds, such as saponins, quinoa proteins, polyphenolic compounds and 20-hydroxyecdysone by yet unknown mechanisms (Simnadis et al, 2015). Considering the attributes and potential to contribute to food security worldwide, the draft genome sequence of an inbred line has been recently published, comprising a free-access Quinoa Genome DataBase (QGDB), which will provide insights into the mechanisms underlying agronomically important traits of quinoa (Yasui et al, 2016).…”
Section: Introductionmentioning
confidence: 99%